The role of nonrandomized trials in the evaluation of oncology drugs. Issue 5 (7th April 2015) - Simon, R; Blumenthal, GM; Rothenberg, ML; Sommer, J; Roberts, SA; Armstrong, DK; LaVange, LM; Pazdur, R
<x xml:space="preserve">Abstract</x> Although randomized trials provide the most reliable evidence of a drug's safety and efficacy, there are situations where randomized trials are not possible or ethical. In this article we discuss when and how single‐arm trials can be used to support full approval of oncology drugs. These include situations in which an unprecedented effect on tumor response is observed in a setting of high unmet medical need, clinical trial patients have been well characterized, enabling a target population to be clearly defined, experience exists in a sufficient number of patients to allow adequate assessment of the risk:benefit relationship, and a proper historical context can be provided for analysis. We also discuss how response rates might be considered predictive of long‐term outcomes or clinically meaningful in and of themselves in certain contexts.